2018
DOI: 10.1016/j.ebiom.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Concurrent Tuberculosis and Diabetes Have a Pro-Atherogenic Plasma Lipid Profile

Abstract: BackgroundType 2 diabetes mellitus (DM) is a major risk factor for development of tuberculosis (TB), however the underlying molecular foundations are unclear. Since lipids play a central role in the development of both DM and TB, lipid metabolism may be important for TB-DM pathophysiology.MethodsA 1H NMR spectroscopy-based platform was used to determine 225 lipid and other metabolic intermediates in plasma samples of healthy controls (n = 50) and patients with TB (n = 50), DM (n = 50) or TB-DM (n = 27).Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 52 publications
5
55
0
2
Order By: Relevance
“…In our study we observed that the HDL level of DM and TB patients was at 34.17 mg/dl, the baseline HDL level of DM free TB patients was at 43.49 mg/dl. The nding was in line with the nding in Netherland [41], suggesting high malnutrition burdens in the study area [42].…”
Section: Discussionsupporting
confidence: 87%
“…In our study we observed that the HDL level of DM and TB patients was at 34.17 mg/dl, the baseline HDL level of DM free TB patients was at 43.49 mg/dl. The nding was in line with the nding in Netherland [41], suggesting high malnutrition burdens in the study area [42].…”
Section: Discussionsupporting
confidence: 87%
“…An increased fasting serum TG concentration has been associated with coronary artery disease, increased mortality risk in coronary heart disease (CHD) patients, and an increased risk for developing both CHD and ischemic heart disease . Next to this, higher VLDL lipoprotein concentrations have been associated with ischemic heart disease risk, and higher levels of VLDL‐TG have been observed in type 2 diabetes mellitus patients . Thus, the effects of the MED diet, for example, the lowering of total VLDL‐TG, and serum TG concentration, may indicate a potential additional beneficial effect on cardiovascular risk on top of the effect of the MUFA content.…”
Section: Discussionmentioning
confidence: 99%
“…1B) that was shown to be increased in patients in the study of Weiner et al 3 and Vrieling et al 13 . However, in a study of a TB patient cohort from South Africa, also a decreased level of phenylalanine was reported compared to the control group 30 .…”
Section: Metabolite Profiles Of Tb Patients Measured By Mass Spectrommentioning
confidence: 96%